Expertise and the making of World Heritage policy. Issue 1 (2nd January 2017) - James, Luke; Winter, Tim
Abstract : This paper contributes to two emergent areas of scholarship: first, the role of expertise within the domain of cultural heritage practice; and second, international heritage institutions and their processes of governance. It does so by exploring expertise within the context of World Heritage Committee meetings. These forums of international heritage policy formulation have undergone significant changes in recent years, with larger geopolitical forces increasingly shaping process and decisions. This paper foregrounds the idea of these annual meetings as 'locales' in order to explore the inflows of expertise that help constitute authoritative decision-making, how expert knowledge is crafted for and by bureaucratic structure, and how the interplay between technical knowledge and politics via an 'aesthetics of expertise' bears upon future directions. In offering such an analysis, the paper seeks to add nuance and conceptual depth to our understanding of international conservation policy and the regulatory, governmental practices of organisations such as UNESCO.